Comparative study on the effect of organic waste on lauric acid produced by hermetia illucens larvae via bioconversion - Leong, S.Y. (Taylor's University, 2015)
Bioconversion by Hermetia illucens larvae using three types of organic waste via fruit waste, palm decanter cake and treated sewage sludge as low fat feed has been investigated in this study. Hermetia illucens larvae were used to transform the organic waste into higher value product. The present study examines the effect of feed types on the fatty acid composition particularly on lauric acid, C12:0 metabolized by Hermetia illucens larvae. In order to investigate the effect of feed on larvaeâsâ fatty acid composition, the proximate analyses were carried out to determine the feed composition prior feeding to the larvae. The composition analysis of lipid content found in the feed were 0.57Â±0.47 , 1.24Â±0.06 and 12.92Â±0.68 from treated sewage sludge, fruit waste and palm decanter, respectively. It was evident that, there was an increased in lipid content found in the larvae biomass derived from sewage sludge, fruit waste and palm decanter. The results revealed that, the amount of lipid produced by the larvae biomass were 29.85, 44.46 and 36.51 derived from the sewage sludge, fruit waste and palm decanter cake, respectively. Besides that, the fatty acid produced by the larvae has higher saturated fatty acids than unsaturated fatty acids. The total saturated fatty acid produced by Hermetia illucens larvae fed with treated sewage sludge, fruit waste and palm decanter was 81.95, 91.79 and 76.47, respectively. Despite feeding with assorted feed, the most abundance compositions of fatty acid were lauric acid, C12:0. The highest amount of lauric acid produced from the larval biomass was 76.13 fed with fruit waste. Â© School of Engineering, Taylorâs University.